Porcupine bezoar exhibit cell cycle arrest through inhibiting cyclin /CDK1 complex and apoptosis mitochondria mediated dependent pathway in A549 cells - Firus Khan, Al'aina Yuhainis; Abdullah Asuhaimi, Faizah; Abdull Rasad, Mohammad Syaiful Bahari; Mohamad, Mardhiah; Hashim, Ridzwan; Mamat, Suhana; Johan, Muhammad Farid; Abdul Wahab, Ridhwan (2016)
Porcupine bezoar (PB) previously reported to possess various medical properties, however there is no information on its potential anticancer effect on human cancer cells. In this study we investigate potential apoptotic effects induced by PB extracts in A549 cells and elucidate the underlying mechanism. Our study revealed that PB reduced the viability of A549 cells in dose dependent manner. PB treatment shown induction morphological changes of apoptosis feature in our phase contrast, hoechst 33342 and rhodamine phalloidin counter staining analysis. Flow cytometric analysis revealed that PB led to cell cycle arrest at G0/G1 through promoting p21 and inhibiting cyclin D/CDK1 complex gene expressions. Apoptotic gene expressions results indicated that PB mediated apoptosis of A549 cells by mitochondria pathway through receptor. Evidenced up-regulation of caspase 8 and BCL-2 interacting domain (BID) supported which resulted in Cytochrome C released. Additionally, upregulation of Bax result in down regulation of Bcl-2. The activities of caspase-8 and caspase-9 were enhanced by PB promoting caspase-3 activation, leading to DNA fragmentation. In conclusion, PB induced apoptosis occurs via mitochondria dependent pathway through receptor.